Aplikasi Metode Geolistrik dan Analisis X-Ray Diffraction (XRD) untuk Investigasi Longsor di Pidada, Kecamatan Panjang, Bandar Lampung - Mulyasari, Rahmi; Suharno; Haerudin, Nandi; Hesti; Yogi, Ida Bagus Suananda; Saputro, Sugeng Purwo (BRIN Publishing, 2021)
Bandar Lampung is a densely populated urban area consisting of land and water with several plateaus and mountains that stretch across this region. To support sustainable development in a city area, it is necessary to have a regional arrangement concept that considers all aspects, one of which is the potential disaster aspect. One of the potential disasters in Bandar Lampung, especially in Panjang District is a mass movement/landslide. Based on previous research, this area has been recorded as having several historical points of landslides, but there is no mitigation/response specifically for this type of disaster. The purpose of this study was to determine the arrangement of rocks that are in the landslide-prone zone in Panjang District using the geoelectric resistivity method and to analyze the soil engineering assessment obtained from the results of lithological analysis using X-Ray Diffraction (XRD). The results of the geoelectric analysis indicate that there are three lithological layers in the study area; namely tuff sediments with resistivity values and depths between (1–40 Ωm; 0.4–4 m), clay sand (40–120 Ωm; 2–4 m), and solid breccias with igneous rock components (>120 Ωm; 2–22 m). Furthermore, based on the results of the analysis of soil engineering assessments, tuff sediment as a surface layer that has experienced landslides has been identified as having susceptible lithological engineering properties because it has undergone quite intensive oxidation and weathering. The data obtained is expected to be used as supporting data for disaster potential-based regional planning.